Projeto e implementação de dispositivo eletrônico inteligente flexível para aplicações em Smart Grid - Santos, Tállyson da Silva (2018)
According to the International Energy Agency/USA (IEA): “a smart grid (SG) is an electricity grid that uses digital technology to monitor and manage the transportation of electricity from all sources of generation, finding a variety of demands and users. These networks will be able to coordinate the needs and capabilities of all generators, operators, end-users and stake holders of the electricity market in order to optimize the use and operation of the assets in the process, minimizing environmental costs and impacts while maintaining reliability, resilience and stability of the system”. In this context and looking for the integration and convergence of different systems to incorporate an infrastructure of a SG, this work presents the mathematical modeling, design and implementation of a flexible intelligent electronic device (IED). The proposed IED differs from the existing IEDs presenting flexibility, being able to realize the acquisition of different variables (voltage, current, temperature, pressure, etc.) with different conditioning values, furthermore, the conditioning is carried out by software. The IED can operate as a smart meter, as a dynamic controller (local) and/or as a supervisory controller, thus improving the efficiency, reliability and security of the system. Other advantages of the proposed IED are: low cost, versatility (changes can be made by software), high processing capacity (ARM processor), communication features (hybrid network architecture (HNA)), easy integration (interoperability), easy maintenance (modularity) and scalability.